Pengaruh Gaya Kepemimpinan terhadap motivasi Kerja karyawan pada PT. Bess Central Insurance Jakarta - Fransiscus Amonio Halawa; Budi Ariyanto; Gregorius Duli L (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2023)
ABSTRACT The purpose of this study is to determine the leadership style at PT. Bess Central Insurance, to determine employee motivation at PT. Bess Central Insurance and to determine the effect of leadership style on employee motivation at. researchers conducted research to obtain the necessary data. The location of this research was carried out at PT. Bess Central Insurance Jakarta. The population in this study are all employees at PT. Bess Central Insurance as many as 70 people. In this study the researchers used observation and interviews as a technique to collect data from respondents. The results showed that the leadership style of the leader at PT. Bess Central Insurance has not been able to increase employee motivation, employee motivation at PT. Bess Central Insurance can be categorized as low and leadership style has a strong influence on work motivation, meaning that if the leadership style is better it will affect the increase in employee motivation and vice versa if the leadership style is not good then employee motivation will decrease. Keywords: Leadership style, employee motivation